Management of anidra w.s r to insomnia using marma therapy - A case study - Dr Jyothi.V; Dr Bandapalle Dattu Narayanrao (The Bioscan, 2025)
According to Ayurveda, the three primary pillars of the body are Brahmacharya, Nidra, and Aahara. One of the thirteen urges that cannot be controlled is Anidra. Anidra, or lack of sleep, is classified under the Vatananatmaja Vikara in Ayurveda and is caused by an aggravation of the Vata Dosha. Transquillizers are prescribed by modern medicine to cure sleeplessness. These medications provide significant relief during the first few days of treatment, but prolonged and ongoing use leads to negative side effects. A 40-year-old woman arrived at the outpatient department complaining of having trouble falling and staying asleep for the past eight months. One of the 108 marmas listed in Tamil varmology, Urakkakala marma is situated on both sides of the inner side of the lower jaw. Stimulation of urakkakala marma was done and the patient's subjective parameters showed significant improvement. In Anidra (insomnia), marma therapy may be safe, efficient, easily accessible, reasonably priced, and free of adverse effects.